Modelling hepatitis C virus kinetics during treatment with pegylated interferon α-2b: errors in the estimation of viral kinetic parameters - Shudo, E. (2008)
Neumann et al. [1] developed a widely used model for the analysis of hepatitis C virus (HCV) dynamics after the initiation of interferon therapy that assumes the effectiveness of therapy in blocking virion production, ε, is constant. However, with pegylated interferon α-2b (PEG-IFN) given weekly, there are significant changes in drug concentration between doses, leading to changes in drug effectiveness and viral rebounds. To investigate the appropriateness of the constant effectiveness (CE) model [1] for studies involving PEG-IFN, we simulated PEG-IFN treatment, using 294 sets of pharmacokinetic/pharmacodynamic (PK/PD) parameters that span observed ranges and fit the simulated data to the CE model. For most combinations of PK/PD parameters, the fits resulted in an infected cell loss rate, δ, that underestimates the true value used in the simulations and yielded over-estimates of the average effectiveness of PEG-IFN. In the setting of PEG-IFN therapy, the use of the CE model of HCV kinetics has to be reevaluated and the validity of its use depends on the amount of HCV RNA rebound observed between doses.